Sustainability perceptions of Community Based tourism by stakeholders in Central Asia. Issue 2 (3rd July 2021) - Alieva, Deniza; Usmonova, Gulnoza
ABSTRACT: The present study is focused on community-based tourism (CBT) having as its primary purpose the analysis of benefits that community can obtain or perceive like the ones got from the tourism. CBT can be used as a powerful tool to improve the livelihoods of people who call their destination home and to combat poverty in Central Asia. The following study presents a review of CBT as a concept and provides data collected in the field on the sustainability perceptions of CBT from stakeholders. The information helped determining long-term goals for sustainability planning and suggesting an action strategy for sustainable tourism development so the government can apply it into practice.